Kingdom hearts 358/2 days. 2 - Amano, Shiro (Yen Press, 2014)
"When Xion loses her Keyblade, it's Roxas's job to make sure no one finds out. As long as the two can go on missions together, no one will know that it's Roxas collecting all the hearts. But will Demyx blow their little secret?!" -- p. [4] of cover.